Native parasitoids in pine shoot moth control (Rhyacionia buoliana): a functional complex? - Lanfranco, Dolly M.; Aguilar, Angélica M.; Horcos, Rodrigo A.; Büchner, Jaime F. (Bosque (Valdivia), 1994)
The control incidence of each of the native parasitoids associated with Rhyacionia buoliana Schiff. is informed. The efficacy of these biocontrol agents and the projection of the generalist-specialist relation in this case of forest importance is commented. Coccygomimus fuscipes (Brullé) appears as the only species able to complement the parasitism exerted by Orgilus obscurator Ness.